2023
DOI: 10.1088/1755-1315/1187/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Maize Plant Height Using Unmanned Aerial Vehicle (UAV) RGB based on Digital Surface Models (DSM)

Abstract: Maize (Zea mays L.) is one of the essential agricultural products in Papua Province of Indonesia, specifically in the three largest maize producing regions, namely Nabire Regency, Biak Numfor Regency and Merauke Regency, with the number of productions of 991 tons, 764 tons, and 751 tons respectively in 2015. Unfortunately, since 2016 the secondary data on food crops productivity, including maize, has not been provided yet in the provinces statistical report, due to manual estimation methods, i.e., visual estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For instance, the Indonesian Government in Presidential Decree No 5/2006 states the target of 25% share of renewable energy (RE) by 2021; unfortunately, the RE production is only about 3%. The situation explains why bioenergy development in this country is supported and encourages the potentiality of waste from raw materials for energy utilization [28]. Currently, Indonesia has been producing and marketing biodiesel from palm oil.…”
Section: B Sago For Biomass and Bioenergy Productionmentioning
confidence: 99%
“…For instance, the Indonesian Government in Presidential Decree No 5/2006 states the target of 25% share of renewable energy (RE) by 2021; unfortunately, the RE production is only about 3%. The situation explains why bioenergy development in this country is supported and encourages the potentiality of waste from raw materials for energy utilization [28]. Currently, Indonesia has been producing and marketing biodiesel from palm oil.…”
Section: B Sago For Biomass and Bioenergy Productionmentioning
confidence: 99%
“…The initial UAV flight performed on the day of maize sowing was utilized as the reference digital terrain model (DTM). For the subsequent time points (20,29,37,44,50,61, and 71 days after sowing), image processing led to the creation of digital surface models (DSMs) [14,15,[38][39][40]. These DSMs were then input into QGIS software, where Equation ( 1) was applied to generate the DEM values corresponding to each assessment date.…”
Section: Extraction Of Vegetation Indices and Digital Elevation Modelmentioning
confidence: 99%
“…Multiple examples of accurate plant height estimates using UAV imagery have been shown in crops such as barley (Hordeum vulgare L.) (Bendig et al, 2014;Herzig et al, 2021), cabbage (Brassica oleracea var. capitata L.) (Moeckel et al, 2018), cotton (Gossypium hirsutum L.) (Feng et al, 2019;Liu et al, 2020), eggplant (Solanum melongena L.) (Moeckel et al, 2018), faba bean (Vicia faba L.) (Ji et al, 2022), maize (Anthony et al, 2014;Geipel et al, 2014;Grenzdörffer, 2014;Su et al, 2019;Varela et al, 2017;Anderson et al, 2019;Malambo et al, 2018;Shi et al, 2016;Tirado et al, 2020;Adak, Murray, Božinović, et al, 2021;Letsoin et al, 2023), potato (Solanum tuberosum L.) (de Jesus Colwell et al, 2021;Xie et al, 2022;Njane et al, 2023), rapeseed (Brassica napus L.) (Xie et al, 2021), sorghum (Sorghum bicolor L.) (Chang et al, 2017;Shi et al, 2016;Watanabe et al, 2017;Gano et al, 2021), soybean (Glycine max L.) (Li et al, 2022), tomato (Solanum lycopersicum L.) (Moeckel et al, 2018), and wheat (Triticum aestivum L.) (Holman et al, 2016;Madec et al, 2017;Michalski et al, 2018;Volpato et al, 2021). Studies on plant height using UAVs have shown variable levels of success when compared to manual measurements due to plant structure, field layout, and improvements in best practices as more research was completed (Holman et al, 2016;Sweet et al, 2022).…”
Section: Introductionmentioning
confidence: 99%